The Alt-right's Discourse on "Cultural Marxism": A Political Instrument of Intersectional Hate - Mirrlees, Tanner (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
This article analyzes the history, production, circulation, and political uses of the alt-right’s discourse about cultural Marxism in the context of the right-wing populist Trump presidency, the rise of fascist movements in the United States and worldwide, and the politics of intersectional hate.